Horror, hubris and humanity: the international engagement with Africa, 1914–2014 - Reid, R (Oxford University Press, 2014)
This article examines the international engagement with Africa from the First World War and the apex of colonial rule through to the present day. It is argued that there have been dramatic shifts throughout this period—from increasing interventionism on the part of the colonial state, to decolonization and the emergence of nation-states with independent foreign policy programmes, to the predations and influences of the Cold War, to the developmentalism and humanitarianism of the contemporary era. Yet, there has also been marked continuity in terms of policy, perception and practice. In particular, Africa has long been seen in terms of economic opportunity—a place where markets and raw materials abound—and of military and political threat, a place in which intrinsic instability makes external intervention both desirable and inevitable. While immediate contexts have changed over time, the international engagement with the continent remains essentially economic and military. A concern for democratization and development represents a relatively new element, although even this can be traced to the paternalistic humanitarianism of the colonial era and, earlier still, moral stances toward Africa in the nineteenth century.